Collaboration and Knowledge Sharing via Facebook Groups: Analysis of Postings of Library and Information Science Community - Das, Kshirod; Mahapatra, R.K. (DESIDOC Journal of Library & Information Technology, 2018)
Social networking sites are visibly the latest trend and have changed the way the 21st century communicates each other. Its usage becomes more and more in the world of information, its presence in the library and information science becomes challenging and exciting. The aim of this study was to know the trend of posting, sharing, commenting and like a Facebook post, to understand the participation level and response against Facebook group post, and also to explore the type of content generated by LIS community through Facebook Group. Group postings/contents of four different Facebook Group Pages (“LIS Group, LIS-XPRESS, S.M.I.T. Library Students, Students of LIS”), operating and use by LIS Community during the period February 2012 to February 2015 are collected, read and analyzed. The analysis of those contents found that sharing photos, links and statuses are major types of group posts in every group and members hardly posting videos and create events for the community.